Development and Validation of a Prognostic Signature Based on Immune Genes in Cervical Cancer - Chen, Yu; Lin, Hao; Pi, Ya-Nan; Chen, Xi-Xi; Zhou, Hu; Tian, Yuan; Zhao, Wei-Dong; Xia, Bai-Rong (Frontiers in Oncology, 2021)
Background: Cervical cancer is one of the most common types of gynecological malignancies worldwide. This study aims to develop an immune signature to predict survival in cervical cancer. Method: The gene expression data of 296 patients with cervical cancer from The Cancer Genome Atlas database (TCGA) and immune-related genes from the Immunology Database and Analysis Portal (ImmPort) database were included in this study. The immune signature was developed based on prognostic genes. The validation dataset was downloaded from the Gene Expression Omnibus (GEO) database. Result: The immune signature namely immune-based prognostic score (IPRS) was developed with 229 genes. Multivariate analysis revealed that the IPRS was an independent prognostic factor for overall survival (OS) and progression-free survival (PFS) in patients with cervical cancer. Patients were stratified into high IPRS and low IPRS groups, and those in the high IPRS group were associated with better survival, which was validated in the validation set. A nomogram with IPRS and stage was constructed to predict mortality in cervical cancer. Conclusions: We developed a robust prognostic signature IPRS that could be used to predict patients’ survival outcome.